Chromatin accessibility directly governs flavonoid biosynthesis and indirectly orchestrates cannabinoid production in Cannabis - Ma, Yuanchang; Wei, Xiuye; Zhou, Weixin; Xie, An; Chen, Yongzhong; Yang, Chen; Chen, Lingcheng; Dong, Linlin; Ning, Kang (Frontiers in Plant Science, 2026)
Secondary metabolites in hemp enhance its pharmaceutical and nutraceutical value, yet the epigenetic regulatory network underlying secondary metabolite biosynthesis remains poorly understood in hemp. Here, we profiled the inflorescences of two cultivars with different trichome density by integrating metabolomics, transcriptomics and ATAC-seq. Multi-omics data revealed pronounced differences in metabolites (491 differentially accumulated metabolites (DAMs)), transcripts (8343 differentially expressed genes (DEGs)), and chromatin accessibility (11376 different accessibility genes, (DAGs)) between two cultivars. Integrated analyses reveal that increased chromatin accessibility at the promoters of several flavonoid-biosynthetic genes up-regulated their expression, resulting in the accumulation of flavonoids. Although chromatin accessibility of cannabinoid biosynthetic gene promoters modulates content, differential chromatin accessibility of the promoter of fatty acid biosynthetic and trichome density (trichome initiation, MeJA signaling, and identity of floral organ) related genes constitutes the key driver underlying cannabinoid divergence between two cultivars. Our study advances the understanding of epigenetic regulation of plant secondary metabolites and offers a novel strategy for enhancing cannabinoid and flavonoid content in Cannabis, providing efficient and precise molecular markers for the selection and breeding of new cannabis varieties.